Implementing PEN-FAST for penicillin allergy delabeling in a high-prevalence population - Göcebe, Deniz; Kommoss, Katharina; Hartmann, Martin; Enk, Alexander; Schäkel, Knut (Journal der Deutschen Dermatologischen Gesellschaft, 2026)
Background and objectives Self-reported penicillin allergies lead to the use of broad-spectrum antibiotics, increase drug resistance, and constitute an economic burden. The PEN-FAST score aims to identify low-risk patients for direct drug provocation tests (DPT) without prior skin testing with a reported negative predictive value (NPV) of over 95%. Patients and methods In this single-center study (Department of Dermatology, University Hospital Heidelberg, Germany), the PEN-FAST score was evaluated for patients carrying a penicillin allergy label between 2004 and 2024. Skin testing, allergen-specific IgE, and consecutive DPT were performed. Results A total of 189 patients were analyzed. In a retrospective cohort, 106 of 149 patients showed negative skin tests and received DPT, leading to the delabeling of 99 patients (66.4%). PEN-FAST identified 55 of 149 (36.9%) as low-risk, of which three low-risk patients were misclassified. In a prospective PEN-FAST low-risk cohort, one of 40 patients showed a mild reaction after DPT. Overall, NPVs of both PEN-FAST and formal allergy testing were 95.8%. Conclusions Our results advocate for direct DPT in patients carrying a penicillin allergy label classified as low-risk by PEN-FAST. PEN-FAST demonstrated high NPV, safety, and feasibility in a cohort with a high prevalence of true allergies.